Numerical analysis of three-dimensional acoustic field with background flow using constrained interpolation profile method. (14th June 2018) - Fukuda, Akihiro; Okubo, Kan; Oshima, Takuya; Tsuchiya, Takao; Kanamori, Masashi
Abstract: Our study group is investigating the acoustic simulation with background flow using the constrained interpolation profile (CIP) method. The CIP method is a type of method of characteristics (MOC) used for time domain numerical analysis. In this study, we examine the calculation method considering background flow using the type-C and type-M CIP methods. The type-C CIP method involves the calculation of all advection equations using the cubic Hermite interpolation, whereas the type-M CIP method involves the calculation of advection equations of spatial differential value perpendicular to the propagation direction using linear interpolation. We compare the calculation results with those of other methods and evaluate calculation accuracy, calculation time, and memory cost. Results show that our proposed method maintains high accuracy under various environmental conditions and that the proposed method is superior in terms of calculation time and memory cost.